Storylines and imaginaries of wastewater reuse and desalination - The rise of local discourses on the Swedish islands of Öland and Gotland - Maria Takman; Michael Cimbritz; Åsa Davidsson; Lea Fünfschilling (Water Alternatives, 2023)
Increased pressure on existing freshwater resources has given rise to interest in new raw water sources. Wastewater reuse and desalination are two alternatives that are frequently compared and discussed in the literature. In this study, local discourses in the form of storylines and imaginaries were identified on the Swedish islands of Öland and Gotland. These local storylines and imaginaries were then compared to those found in the literature on wastewater reuse and desalination; in the process, overlaps and variations were identified. On Gotland, a controversy over desalination was observed where arguments were raised for and against 'natural' (nature-based and therefore 'good') solutions and 'unnatural' or engineered solutions (desalination). Such a controversy was not observed on Öland. The controversy on Gotland arose out of competing imaginaries of the future. Such discourses can affect the transitions of water systems. Understanding local discourses may thus be crucial to our understanding of the larger transitions underway in the water sector and may figure importantly in the acceptance of new water sources.